Harmonising legality with morality in Islamic banking and finance: A quest for Maqāṣid al-Sharī‘ah paradigm - Zakariyah, Luqman (Intellectual discourse, 2015)
Scholars in Islamic Finance Industry (IFI) have been calling for the integration of Islamic morality with legal theories in the industry. Among the reasons for this call is an unethical trend in product innovation. Implementing Islamic banking and financial practices would require adopting their undergirding Islamic legal and moral frameworks. Departing from these foundations of Islamic law could render the activities conducted under its name religiously unacceptable. Many approaches have been put forward to achieve this cause. One of the most complex yet subjective approaches is the quest for Maqāṣid al-Sharī‘ah. This paper critically examines the feasibility of harmonising morality with legality in Islamic finance. In doing so, it will reveal what constitutes morality and legality in Islamic legal theory, and critically examine the approaches of Muslim classical scholars in fusing the two elements together for the realisation and actualisation of the very objectives of Sharī‘ah. Questions of the relationship between morality and legality are raised, and samples of Islamic finance products are evaluated to expose their moral and legal dimensions. Lastly, the role of Maqāṣid al-Sharī‘ah in the process of harmonisation is discussed with some observations and reservations on the practicality of their implementation.